Mass movement processes in unconsolidated Pleistocene sediments - A multi-method investigation at the Hochgraben (Jenbach/Upper Bavaria) - Wetzel, Karl-Friedrich; Sass, Oliver; v. Restorff, Cai (ERDKUNDE, 2006)
Mass movement processes in the Alps pose enormous hazard. Due to the observed and predicted climatic change the chances are that mass movement processes will increase in future. At the Hochgrabenrutschung in the Jenbachtal near Rosenheim (Upper Bavaria) sliding processes are taking place in Pleistocene loose sediments, consisting of moraines and layered sediments of ice dammed lakes from the Inn-Glacier. Pleistocene loose sediments are a common appearance in the Bavarian Alps. The focus of the current investigation was an examination of the regional extent and the underground structure of the sliding masses, as well as the reasons for sliding and the technical possibilities of influencing the mass movement by use of different methods as classical geomorphological methods (mapping, drilling) and geophysical techniques (Earth Resistivity Tomography - ERT and Ground Penetrating Radar - GPR). Also, a comparison of the different methods of investigation has been conducted. The following results can be summarized. A broad spectrum of different investigation methods can be seen as very useful in producing reliable results in the complex field of mass movement examination. Classical geomorphological methods are very time consuming and the spottiness of drilling results may lead to misinterpretations. In contrast, geophysical methods deliver results quite quickly, but results are reliable only if verification by classic methods has been done. In the Pleistocene loose sediments of the Hochgrabenrutschung ERT was very useful in detecting ground structures along different transects. Due to the high water content of the sediments the GPR technique failed and only near surface structures have been detected. The reasons for the sliding processes at the Hochgraben must be seen in the loose sediments, which obviously have been built up in two phases. The unconsolidated sediments of the near surface underground consist of an alteration of sandy pebbles and varvic clays. These sediments are underlain by compacted Pleistocene Sediments (Nagelfluh) acting as a slipping face. The Flysch layers in the deeper underground are not involved in the mass movement processes. Good drainage of the upper part of the sliding masses and by-passing of the overland flow of the forest roads, now entering the sliding mass, seem to be the major technical possibilities to reduce mass movement hazard. A dam built up at the lower part of the sliding mass by the water authority seem to have only a reduced influence on the mass movement processes acting in the upper part.